Stocks and flows of natural and human-derived capital in ecosystem services. (March 2016) - Jones, L.; Norton, L.; Austin, Z.; Browne, A.L.; Donovan, D.; Emmett, B.A.; Grabowski, Z.J; Howard, D.C.; Jones, J.P.G.; Kenter, J.O; Manley, W.; Morris, C.; et al.
Highlights: Realised ES are a product of the potential service and specified beneficiaries. Natural capital (NC) and human-derived capital (HDC) are both essential for ES. HDC plays a role even at the stage of potential ecosystem services. It is possible but not always easy to separate the contribution of NC and HDC to ES. Sustainable management should identify critical NC and HDC for each service. Graphical abstract: Abstract: There is growing interest in the role that natural capital plays in underpinning ecosystem services. Yet, there remain differences and inconsistencies in the conceptualisation of capital and ecosystem services and the role that humans play in their delivery. Using worked examples in a stocks and flows systems approach, we show that both natural capital (NC) and human-derived (produced, human, social, cultural, financial) capital (HDC) are necessary to create ecosystem services at many levels. HDC plays a role at three stages of ecosystem service delivery. Firstly, as essential elements of a combined social-ecological system to create a potential ecosystem service. Secondly, through the beneficiaries in shaping the demand for that service. Thirdly, in the form of additional capital required to realise the ecosystem service flow. We show that it is possible, although not always easy, to separately identify how these forms of capital contribute to ecosystem service flow. We discuss how applying a systems approach can help identify critical natural capital and critical human-derived capital to guide sustainable management of the stocks and flows of all forms of capital which underpin provision of multiple ecosystem services. The amount of realised ecosystem service can be managed in several ways: via the NC & HDC which govern the potential service, and via factors which govern both the demand from the beneficiaries, and the efficiency of use of the potential service by those beneficiaries.